EXAMINING BUSINESS ETHICS IMPLEMENTATION IN CORPORATE CULTURE OF AQUA GROUP - Rahmadhi, Regina Parahita (Jurnal Ilmiah Mahasiswa FEB, 2016)
AQUA Group is one of leading manufacturing companies in Indonesia that has run the business for more than 40 years. The sustainability of the company must be established on a supportive management and a particular culture. Thus, this research aims to examine business ethics of AQUA Group through its corporate culture. By this research, it is expected to explore whether the company has been ethical in treating people and environment, instead of conducting beneficial business only. This qualitative study was taken in AQUA Group – PT. Tirta Investama (TIV) Pandaan. The methods used in collecting data were observation in Pandaan plant, as well as interview to employees and residents living around the plant. Based on the research results, it was found that personal values of local employees in PT. TIV Pandaan are more dominant than the culture designed by the foreign company (French). This disparity occurs because there is a cultural relativism between Danone Group management and Indonesian local community. Even though the implementation of corporate culture in field is different with the way it is set, the existence of ethical relativism theory supports that the way of employees establish their own culture is ethical based on their local values.Keywords: business ethics, corporate culture, AQUA Group, PT. TIV Pandaan